Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/adem.201300259
|View full text |Cite
|
Sign up to set email alerts
|

Sand Supported Mixed‐Phase TiO2 Photocatalysts for Water Decontamination Applications

Abstract: Abstract:Using an organometallic precursor, TiO 2 coatings were fabricated on surfaces of quartz, zircon and rutile sands. X-ray Diffraction, X-ray Fluorescence, UV-Vis spectroscopy and surface area measurement were used to characterise support materials. The phase composition and morphology of the coatings were characterised by laser Raman spectroscopy and SEM respectively. A packed bed reactor was used to study the inactivation of Escherichia coli in recirculating water by the supported photocatalysts. It wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 47 publications
0
31
1
Order By: Relevance
“…(Khalilian et al, 2015;Sarkar et al, 2015;He et al, 2016;Vaiano et al, 2015;Hanaor and Sorrell, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…(Khalilian et al, 2015;Sarkar et al, 2015;He et al, 2016;Vaiano et al, 2015;Hanaor and Sorrell, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Hence, activation of the diatomite surface becomes necessary for removal process optimization. Photocatalytic nature of TiO 2 has been utilized in the environmental remediation studies (Hanaor et al 2011;Hanaor and Sorrell 2014;Yang et al 2012;Lasek et al 2012;Kujawa et al 2013;Kamegawa et al 2013). Wu et al (2009) reported visible light-induced photocatalytic inactivation of bacteria with nitrogen-doped TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth tungstate coatings are often described as efficient visible light-activated photocatalytic materials [15], however, they are usually produced by chemical methods, e.g., hydrothermal methods [13,14] or electrospinning [22]. Use of photocatalyst-coated particulates is frequently reported for water treatment applications, however, chemical methods are typically used for the coating's deposition [23][24][25]. The establishment of a reactive sputter deposition method as a technique for the production of bismuth complex oxides [15,21,26] allows some limitations of these chemical deposition methods, such as the use of hazardous precursors or byproduct formation, to be overcome and provides a simple, yet efficient and readily up-scalable deposition technique.…”
Section: Introductionmentioning
confidence: 99%